Antiviral Activity of Interferon Alpha-2b and Taurine Combination Against SARS-CoV-2 in vitro - N. P. Kartashova; A. V. Ivanina; E. A. Glubokova; I. N. Falynskova; A. A. Poromov; I. A. Leneva (Антибиотики и Химиотерапия, 2022)
Interferons (IFN) have antiviral activity against many viruses, including SARS-CoV-2. A combination of IFN-a2b and the antioxidant taurine is widely used in the Russian Federation, and its antiviral activity has not been studied before. The aim of this study was to determine the antiviral activity of interferon drugs, in combination with taurine and without it. The study included cytotoxicity and antiviral activity assays of IFN-a2b preparations, when stored according to the instructions at 2–8°C, and after 1 month storage at the temperature of 20–26°C in a pre-opened state. The combination of IFN alpha-2b with taurine has a higher antiviral activity compared to IFN alpha-2b mono-preparation by more than 25% at a «low» and 85% at a «high» multiplicity of infection. Selectivity index for combinations of IFN-a2b (50,000 IU/dose) + taurine (1 mg/ml) and IFN-a2b (10,000 IU/ml) + taurine (0.8 mg/ml) was more than 600 units, whereas for the IFN-a2b (10,000 IU/ml) it was 200 units. Antiviral activity does not change after one month at room temperature. The combination of interferon with taurine at high concentrations was less toxic than interferon. The results obtained demonstrate practicability of interferon alpha-2b and taurine combination use for treatment and prevention of COVID-19.